Monitoring Anti-Bribery Enforcement in South Korea: Evidence from OECD - Kiranawat, Waranphat (Korean Studies for International Management Journal, 2026)
This article investigates the implementation and enforcement of the OECD Convention on Combating Bribery of Foreign Public Officials in International Business Transactions (Anti-Bribery Convention) in South Korea by analyzing the Working Group on Bribery’s (WGB) four-phase peer-review monitoring system. Since ratifying the convention in 1999, South Korea has developed a legal framework, which is the Foreign Bribery Prevention Act (FBPA). However, there is a significant gap between formal (de jure) compliance and practical (de facto) enforcement. Through successive monitoring phases, the study identifies South Korea as a condition of “maturity without volition”. This means that South Korea has good institutional structures but lacks the political and judicial will that is important to prosecute powerful economic actors, specifically Chaebols. While phases 1-3 show that South Korea has rapid legislative adoption, phase 4 highlights that South Korea has a declining performance in enforcement and problems that some cases rely on foreign jurisdictions. These problems derive from high levels of secrecy in case detection, narrow interpretations of foreign public officials, and cultural leniency regarding corporate sanctions. Eventually, the article concludes that transitioning to genuine integrity requires moving beyond impractical compliance. So, the article recommends strengthening the judiciary’s understanding of the convention’s principle of functional equivalence and fostering a shift toward proactive and practical risk management within the corporate sector. This will bridge the existing enforcement gap.